Building social and emotional efficacy to (re)engage young adolescents: capitalising on the 'window of opportunity'. Issue 10 (2nd October 2016) - Main, Katherine; Whatman, Susan
ABSTRACT: Research confirms that when students disengage from learning, there is a greatly increased risk of them dropping out of school and not completing secondary education (Year 12). In an Organisation for Economic Co-Operation and Development (OECD) report on Equity in Education [OECD. 2012. " Investing in Equity in Education Pays off ", in Equity and Quality in Education : Supporting Disadvantaged Students and Schools . Paris, France: OECD. doi:10.1787/9789264130852-3-en ], school dropout rates in developed countries averaged 20% and, in some countries, was as high as 25%. Lyche [2010. Taking on the Completion Challenge. A Literature Review on Policies to Prevent Dropout and Early School Leaving . OECD Education Working Papers, No. 53. OECD. doi:10.1787/5km4m2t59cmr-en ] noted that school dropout does not 'just happen' but rather is a long process of disengagement from school. Students entering early adolescence are experiencing rapid and complex changes to their social, emotional, physical, and cognitive development that can positively or negatively affect their experience in education environments. During this time, there is also an increased expectation, both at school and at home, that young adolescents should accept greater responsibility for themselves and their learning. However, when individual students fail to regulate their behaviour or manage the increasing difficulty of the academic work, they can begin to disengage from learning and become entrenched in a downward cycle of poor academic achievement and poor social competence. With an increasing trend in young adolescents to disengage from learning, identifying how to reengage students is critical to their social and academic success. This study reports on the key features of an early intervention programme that targets young adolescent students who are already showing early signs of disengaging from school. Data show that the programme aligns with evidence-based practice and has had a positive effect in promoting and building students' social and emotional efficacy and re-engaging them in learning.